Estimation of a distribution function by an indirect sample - Babilua, P.; Nadaraya, E.; Sokhadze, G. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
The problem of estimation of a distribution function is considered in the case where the observer has access only to a part of the indicator random values. Some basic asymptotic properties of the constructed estimates are studied. The limit theorems are proved for continuous functionals related to the estimation of F^n(x) in the space C[a, 1 - a], 0